Internet das coisas e as agtechs no Brasil - Almeida, Rafael Chiaradia (2019)
The Internet and Information and Communication Technologies (ICTs) are transforming the world economy. Among these technologies is the Internet of Things (IoT), which encompasses a network of machines and devices capable of interacting with each other and which has been the subject of several recent studies. In agribusiness, IoT can contribute to more accurate agriculture by optimizing the use of resources such as fertilizers and water and increasing productivity. Although Brazil has strong and significant competitive advantages in agribusiness, it still has challenges to face, and IoT is a great opportunity for the country to consolidate its world leadership. In January 2018, the Ministry of Science, Technology, Innovation and Communications (MCTIC), published the National IoT Plan, and it defined 8 axes where the application of IoT would be important for the country to reach its goal of becoming the largest exporter of IoT solutions for tropical agriculture. This study aims to analyze Brazilian Agtechs products and/or services according to the list of applications defined in the National IoT Plan. To do this, the agribusiness startups that have developed IoT products and/or services were first mapped, reaching the final number of 23 Agtechs by August 2019. Then, through a documentary analysis on the websites of these companies. and in ezine reports, these Agtechs were characterized and their solutions described, and it was found that, based on the priority axes of the National IoT Plan, only the efficient use of natural resources and inputs has a significant number of active companies. It was also noted that this segment is in growth phase, but with a strong concentration in the Southeast Region, with the state of São Paulo being the main hub. With respect to the IoT architecture layers, only the device and service and application support layers featured a significant number of companies with proprietary solutions. To confirm this data and obtain additional information, a multiple case study was conducted through videoconferencing and teleconferencing interviews with the founders of 4 Agtechs and it was found that field connectivity is the biggest problem faced. Even so, the performance of companies in the network layer is still incipient. The interviews also showed that the information security layer is being covered by more companies than was found in the document analysis.